2008
DOI: 10.1080/15376510701611032
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics in Lung Inflammation:A High-Resolution1H NMR Study of Mice Exposedto Silica Dust

Abstract: Here we report the first (1)H NMR metabolomics studies on excised lungs and bronchoalveolar lavage fluid (BALF) from mice exposed to crystalline silica. High-resolution (1)H NMR metabolic profiling on intact excised lungs was performed using slow magic angle sample spinning (slow-MAS) (1)H PASS (phase-altered spinning sidebands) at a sample spinning rate of 80 Hz. Metabolic profiling on BALF was completed using fast magic angle spinning at 2 kHz. Major findings are that the relative concentrations of choline, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 77 publications
0
45
0
Order By: Relevance
“…We previously demonstrated that lactic acid concentrations are elevated in the lung tissue of mice exposed to silica compared with control mice (11), and on the basis of these data, we examined whether lactate concentrations were also elevated in the lung tissue of patients with IPF. H-PASS NMR spectroscopy of lung tissue homogenates demonstrated that the concentrations of lactic acid were significantly increased in tissue from patients with IPF compared with healthy control subjects (Figures 1A and 1B).…”
Section: Lactic Acid Concentrations Are Elevated In Lung Tissue From mentioning
confidence: 99%
See 2 more Smart Citations
“…We previously demonstrated that lactic acid concentrations are elevated in the lung tissue of mice exposed to silica compared with control mice (11), and on the basis of these data, we examined whether lactate concentrations were also elevated in the lung tissue of patients with IPF. H-PASS NMR spectroscopy of lung tissue homogenates demonstrated that the concentrations of lactic acid were significantly increased in tissue from patients with IPF compared with healthy control subjects (Figures 1A and 1B).…”
Section: Lactic Acid Concentrations Are Elevated In Lung Tissue From mentioning
confidence: 99%
“…High-resolution 1 H nuclear magnetic resonance (NMR) metabolomics using the technique of slow magic angle spinning (i.e., 1 H-PASS) (29), was used to determine the concentrations of lactic acid in fibroblast cell lysates and in whole lung homogenates from patients with IPF and from healthy control subjects using previously reported procedures (11).…”
Section: Nuclear Magnetic Resonance Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the mammalian in vitro systems involved exposing A549 human lung carcinoma cells to cigarette smoke (Vulimiri et al, 2009), human embryonic stem cells to various teratogens (West et al, 2010), and reaggregating neuronal cultures to methylmercury (van Vliet et al, 2008). From in vivo studies, intact organs from exposed experimental animals have been evaluated to include the analysis of intact lung after intratracheal instillation of silica dust (Hu et al, 2008) as well as liver and lung after exposure to 1-nitronaphthalene (Azmi et al, 2005). Also, metabolomics has been able to demonstrate different metabolic responses between mixtures of environmental chemicals.…”
Section: Advantages Of Metabolomics Approach For Environmental Chemicmentioning
confidence: 99%
“…This rapid spinning at this precise angle has the effect of reducing dipolar coupling effects and narrowing of the broad lines found in this tissue. HRMAS-NMR has been applied successfully to analyze different intact cells and tissues [80][81][82][83][84][85], so it seems to be a powerful tool for the analyses of aortic valve tissue.…”
Section: Nuclear Magnetic Resonancementioning
confidence: 99%